openclimatedata/pymagicc: v2.0.0-beta - Zeb Nicholls; Robert Gieseke; Jared Lewis; Sven Willner; Matthias Mengel (Zenodo, 2019)
First steps towards a new interface for Pymagicc, built around OpenSCM's ScmDataFrame